Application of artificial intelligence in wearable devices: Opportunities and challenges. (January 2022) - Nahavandi, Darius; Alizadehsani, Roohallah; Khosravi, Abbas; Acharya, U Rajendra
Abstract: Background and objectives: : Wearable technologies have added completely new and fast emerging tools to the popular field of personal gadgets. Aside from being fashionable and equipped with advanced hardware technologies such as communication modules and networking, wearable devices have the potential to fuel artificial intelligence (AI) methods with a wide range of valuable data. Methods: : Various AI techniques such as supervised, unsupervised, semi-supervised and reinforcement learning (RL) have already been used to carry out various tasks. This paper reviews the recent applications of wearables that have leveraged AI to achieve their objectives. Results: : Particular example applications of supervised and unsupervised learning for medical diagnosis are reviewed. Moreover, examples combining the internet of things, wearables, and RL are reviewed. Application examples of wearables will be also presented for specific domains such as medical, industrial, and sport. Medical applications include fitness, movement disorder, mental health, etc. Industrial applications include employee performance improvement with the aid of wearables. Sport applications are all about providing better user experience during workout sessions or professional gameplays. Conclusion: : The most important challenges regarding design and development of wearable devices and the computation burden of using AI methods are presented. Finally, future challenges and opportunities for wearable devices are presented. Highlights: Applications of artificial intelligence methods such as supervised, unsupervised, etc. in wearable devices are reviewed. Different types of wearable devices are introduced. The body parts on which the wearable devises are installed are investigated. Distribution of existing wearable devices based on target body parts and their applications is presented. Comprehensive treatment of domain-specific applications of wearable devices such as sports, healthcare, industrial and manufacturing is provided. Wearable technologies challenges such as data collection, data transmission, etc. are pointed out. Future directions regarding application of artificial intelligence methods in wearable devices are discussed.